Effect Toxoplasmosis on Thyroid Hormone - Ohood Mozahim Shakir; Redhaa Haider Kamil; Ola Husein Kadum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The study was conducted from January 2021 to March 2022. The study included samples of female patients arriving at some private laboratories in Samarra. The study included (50) serum samples from women arriving at health centers. The study groups were divided into two groups of women, the first group included (35) serum samples from pregnant women who suffered from previous miscarriages, and the second group was the control group, which included 15 samples from healthy women. Blood samples were collected in a volume of (5) ml in clean dry tubes and placed in an incubator at 37°C for (5) minutes, then the coagulated fraction was separated from the clear solution using a centrifuge at a speed of (2000 cycle/min) for (15) minutes. The clear solution represents the blood serum that was drawn using a micropipette, which was divided into (7) parts using plastic tubes, then the samples were kept at a temperature of 20 °C until the required tests were performed on them. Concentrations of thyroid hormon, (T3), (T4) and (TSH), were measured by used the equipment of all test.